ANALYSIS OF THE INFLUENCE OF JOB SATISFACTION, LEADERSHIP BEHAVIOR AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE IN INDONESIA WITH GENERATION AS A MODERATING VARIABLE - Prabowo, Gunawan; Juliana, Juliana (Jurnal Review Pendidikan dan Pengajaran, 2024)
The purpose of the study was to examine and analyze the effect of satisfaction, leadership behavior, and work motivation on employee performance in Indonesia with generation as a moderating variable. This study uses quantitative descriptive methods in this study while collecting data through distributing questionnaires to 200 employees who work in the Jakarta area who work in start-up companies. Data processing techniques carried out include validity tests, reliability tests, and structural equation models (SEM) using SmartPLS software version 3. The results showed that satisfaction has a positive effect, leadership has a positive effect, work motivation has a positive effect on employee performance . Employee performance from the results of the research that has been done is expected to improve the performance of its employees by creating more supportive job satisfaction through good leadership and work motivation as well as building a positive corporate culture where collaboration, support, and teamwork are valued . Implications for further research by conducting preliminary studies and discussions in order to determine the appropriate variables including determining the indicators to be used. While the theoretical implications reveal the application of the right human resource role is the implementation of strategic management at the corporate level can create growth for the company as a whole.